Analysis of the maintenance work order data in educational institutions - Besiktepe Karaman, Deniz, author; Ozbek, Mehmet E., author; Atadero, Rebecca A., author (Colorado State University. Libraries, 2018)
As a part of facilities management (FM), building maintenance activities occupy a significant role in reaching the goal of delivering an acceptable level of performance while minimizing costs and failures. For institutional organizations, an effective FM approach is required to ensure their buildings function properly. Historical work order data may potentially include a substantial value for assessing the condition of building systems by helping to identify common maintenance activities. This study conducts a preliminary analysis of historical work order data collected from six educational institutions in the State of Colorado and Connecticut in the United States between 2008 and 2018.
034 - Deniz Besiktepe Karaman